On piecewise linear processes (2014)
The letter concerns piecewise deterministic processes controlled by a Markov flow with exponentially, Exp (?n), distributed interarrival times T n. Assuming all rates ?n to be different, we study the distribution of a piecewise linear process with jumps. © 2014 Elsevier B.V.